2021
DOI: 10.1002/erv.2823
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of psychotherapy for binge‐eating disorder in a randomized controlled trial: Examining the roles of childhood abuse and post‐traumatic stress disorder

Abstract: Objective To examine childhood abuse and post‐traumatic stress disorder (PTSD) as predictors and moderators of binge‐eating disorder (BED) treatment outcomes in a randomized controlled trial comparing Integrative Cognitive‐Affective Therapy with cognitive‐behavioural therapy administered using guided self‐help. Method In 112 adults with BED, childhood abuse was defined as any moderate/severe abuse as assessed by the Childhood Trauma Questionnaire, lifetime PTSD was assessed via the Structured Clinical Intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…ED-PTSD+ patients endorsed an average of nearly three different types of childhood trauma out of a total of five, which demonstrated a large effect size. This further substantiates the important issue of trauma dose in the development and/or maintenance of EDs and related comorbidities (Ackard & Neumark-Sztainer, 2003;Afifi et al, 2017;Brewerton, 2007Brewerton, , 2018Hazzard et al, 2021;Molendijk et al, 2017;Schoemaker et al, 2002). Our findings are also in line with other research showing that polyvictimization is linked to high degrees of distress and psychopathology (Finkelhor et al, 2014;Haahr-Pedersen et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…ED-PTSD+ patients endorsed an average of nearly three different types of childhood trauma out of a total of five, which demonstrated a large effect size. This further substantiates the important issue of trauma dose in the development and/or maintenance of EDs and related comorbidities (Ackard & Neumark-Sztainer, 2003;Afifi et al, 2017;Brewerton, 2007Brewerton, , 2018Hazzard et al, 2021;Molendijk et al, 2017;Schoemaker et al, 2002). Our findings are also in line with other research showing that polyvictimization is linked to high degrees of distress and psychopathology (Finkelhor et al, 2014;Haahr-Pedersen et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…It may be that the associations between a history of trauma and those ED symptoms at admission (e.g., purging and restricting) were too strong to allow for a history of trauma to additionally predict any deviations from those admission scores. Additionally, while previous studies have found that childhood trauma predicts poor treatment outcome among patients with EDs (Castellini et al, 2018;Hazzard et al, 2021;Mahon, Bradley, Harvey, Winton, & Palmer, 2001;Rodríguez et al, 2005), these results have primarily been in outpatient samples. It is possible that once patients need higher levels of care, such as inpatient, residential or partial hospitalisation programing, their ED pathology has progressed to the extent that it is difficult for more distant factors such as childhood trauma to have a significant impact on treatment outcome.…”
Section: Discussionmentioning
confidence: 96%
“…However, higher ACEs scores were associated with higher binge eating scores, but not purging or restricting, at the end of treatment. Other studies have found that a history of childhood trauma may have a negative impact on treatment outcome for patients with EDs, both in terms of ED symptoms and general psychopathology (Castellini et al., 2018; Hazzard et al., 2021), but it is not clear why a history of trauma might have a negative impact on the improvement of some ED symptoms but not others. It may be that the associations between a history of trauma and those ED symptoms at admission (e.g., purging and restricting) were too strong to allow for a history of trauma to additionally predict any deviations from those admission scores.…”
Section: Discussionmentioning
confidence: 99%
“…Future follow-up studies can confirm if child age of onset is a predictor of response. Rather than duration of illness being a predictor, it may be that the timing and dose of trauma as well as the development of PTSD may adversely affect outcome (Castellini et al, 2018;Hazzard et al, 2021;Scharff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future follow‐up studies can confirm if child age of onset is a predictor of response. Rather than duration of illness being a predictor, it may be that the timing and dose of trauma as well as the development of PTSD may adversely affect outcome (Castellini et al., 2018; Hazzard et al., 2021; Scharff et al., 2021). Although we did not measure hormonal indices in our patients, this traumatized and more symptomatic subgroup may represent an ecophenotype as described by others (Chami et al., 2019; Monteleone et al., 2018, 2020; Teicher & Samson, 2013).…”
Section: Discussionmentioning
confidence: 99%